ANALISIS KEPATUHAN PAJAK PENGHASILAN PASAL 21, PASAL 23 DAN PASAL 4 AYAT 2 PADA PT ABC TAHUN 2023 - Fahrezi, Ramadhani Anhar; Sunani, Avi (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This research aims to analyze PT's compliance. ABC, a company that provides hotel information services, against Indonesian tax regulations. The main focus is on payment and reporting of Periodic Tax Returns for PPh Article 21, PPh Article 23, and PPh Article 4 paragraph 2. Apart from that, this research also aims to identify problems faced by the Accounting Services Office (KJA) which is responsible for this aspect. corporate taxation. The research method used is descriptive qualitative using primary data consisting of Periodic Tax Returns, proof of payment, as well as equalization documents for PPh Article 21, PPh Article 23, and PPh Article 4 paragraph 2 PT. ABC and secondary data from interviews with two informants, namely supervisors and senior staff at KJA. The research results show that overall, PT. ABC was less compliant in fulfilling their tax obligations in the three aspects investigated. Several cases of delays in tax payments and reporting were found, as well as corrections in tax calculations carried out by PT. A B C. Delays in submitting data and changes in data that are not immediately reported as well as a long payment application process within the company are problems faced by the Accounting Services Office (KJA) as a tax consultant for PT. A B C.